2007
DOI: 10.1242/jeb.001560
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for predicting the lifetimes of wave-swept macroalgae: a primer on fracture mechanics and crack growth

Abstract: SUMMARY Biomechanical analyses of intertidal and shallow subtidal seaweeds have elucidated ways in which these organisms avoid breakage in the presence of exceptional hydrodynamic forces imposed by pounding surf. However, comparison of algal material properties to maximum hydrodynamic forces predicts lower rates of breakage and dislodgment than are actually observed. Why the disparity between prediction and reality? Most previous research has measured algal material properties during a single ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 112 publications
(146 reference statements)
1
41
0
Order By: Relevance
“…Estimated rates of productivity, blade erosion, dislodgement of whole fronds and thalli (g dry mass m Hayashida (1977) theless, dis lodgement and erosion are typically greater at sites with high wave exposure than at more protected sites (Duggins et al 2003, Krumhansl & Scheibling 2011a). The measured force to break kelp stipes and blades often exceeds the predicted hydrodynamic force acting on kelps (Utter & Denny 1996, Denny et al 1997, Mach et al 2007), suggesting that breakage and dislodgement are uncommon. For example, Utter & Denny (1996) High erosion and dislodgment rates occur as a result of damage to kelp holdfasts, stipes, and blades.…”
Section: Factors Regulating Production Of Kelp Detritusmentioning
confidence: 99%
“…Estimated rates of productivity, blade erosion, dislodgement of whole fronds and thalli (g dry mass m Hayashida (1977) theless, dis lodgement and erosion are typically greater at sites with high wave exposure than at more protected sites (Duggins et al 2003, Krumhansl & Scheibling 2011a). The measured force to break kelp stipes and blades often exceeds the predicted hydrodynamic force acting on kelps (Utter & Denny 1996, Denny et al 1997, Mach et al 2007), suggesting that breakage and dislodgement are uncommon. For example, Utter & Denny (1996) High erosion and dislodgment rates occur as a result of damage to kelp holdfasts, stipes, and blades.…”
Section: Factors Regulating Production Of Kelp Detritusmentioning
confidence: 99%
“…Relevant fracture mechanics have been recently reviewed (cf. Dorgan et al, 2006;Mach et al, 2007) and can be found in textbooks (e.g. Anderson, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach has involved determination of a seaweed's breaking strength and comparison of this strength with maximal wave-induced force, with breakage often under-predicted (Koehl and Alberte, 1988;Gaylord et al, 1994;Johnson and Koehl, 1994;Friedland and Denny, 1995;Utter and Denny, 1996;Denny et al, 1997;Johnson, 2001;Kitzes and Denny, 2005). Researchers have suggested that other factors, such as damage due to herbivory, abrasion or physiological stressors, may account for observed breakage rates, weakening fronds that individual waves then break (Friedland and Denny, 1995;Utter and Denny, 1996;Kitzes and Denny, 2005;Denny, 2006).Additionally, researchers have investigated the possibility that seaweeds break not just from large individual wave-imposed forces but from damage accumulated over a series of wave-imposed forces (Hale, 2001;Mach et al, 2007a;Mach et al, 2007b;Mach, 2009 Accepted 24 January 2011 SUMMARY Seaweeds inhabiting the extreme hydrodynamic environment of wave-swept shores break frequently. However, traditional biomechanical analyses, evaluating breakage due to the largest individual waves, have perennially underestimated rates of macroalgal breakage.…”
mentioning
confidence: 99%
“…Additionally, researchers have investigated the possibility that seaweeds break not just from large individual wave-imposed forces but from damage accumulated over a series of wave-imposed forces (Hale, 2001;Mach et al, 2007a;Mach et al, 2007b;Mach, 2009 Accepted 24 January 2011 SUMMARY Seaweeds inhabiting the extreme hydrodynamic environment of wave-swept shores break frequently. However, traditional biomechanical analyses, evaluating breakage due to the largest individual waves, have perennially underestimated rates of macroalgal breakage.…”
mentioning
confidence: 99%